Pengaruh Penggunaan Model Problem Based Learning Berbasis Masalah Kontekstual Terhadap Kemampuan Penalaran Matematis Pada Siswa Sekolah Dasar - Lase, Haidir; Dirneti, Dirneti; Indriyani, Desi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This article aims to conduct an in-depth review of various research findings that examine the influence of the contextual problem-based learning (PBL) model on elementary school students’ mathematical reasoning abilities. Problem-based learning positions students at the center of the learning process by presenting problems closely related to real-life situations, thereby encouraging students to explore authentic contexts, connect relevant information, and construct logical and systematic solution strategies. The research method employed is a literature review, with data sources consisting of national and international journals as well as scientific articles relevant to the topic of study. The results of the literature review indicate that the implementation of the PBL model consistently has a positive impact on improving students’ mathematical reasoning abilities, including the ability to identify patterns, formulate generalizations, evaluate the validity of arguments, and connect previously learned mathematical concepts. In addition, problem-based learning has been proven to enhance students’ active engagement, learning independence, and self-confidence in solving mathematical problems. Learning becomes more meaningful because students do not merely follow examples provided by the teacher but are directly involved in the processes of investigation and problem solving. Overall, this article concludes that the contextual problem-based learning model has a significant influence on improving mathematical reasoning abilities and the quality of mathematics learning in elementary schools.